EIB-trained teachers as an example of being «real teachers» for Asháninka bilingual schools of Revitalization - Santos Meza, Edgardo Gregory (2025)
In the central jungle, many academically trained bilingual teachers apply for bilingual positions. The objective of this study is to diagnose the progress and challenges of bilingual teachers with academic and professional training who are in service in bilingual schools in the Chanchamayo-Perené area. The methodology applied is based on the qualitative approach where qualitative face-to-face surveys, online surveys, telephone surveys to teachers, principals and APAFA were applied. Field work was done using the ethnographic method. The results found were different percentages of bilingual teachers with or without pedagogical degrees, bilingual teachers with degrees in related areas without classroom experience. In summary, EIB-trained teachers must meet the formal requirements of their academic training to be recognized as teachers of change in bilingual schools.